2021
DOI: 10.1055/a-1588-0072
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II)/Chiral Carboxylic Acid Catalyzed Enantioselective C–H Functionalization of Sulfoximines

Abstract: Ru(II)-catalyzed enantioselective C–H functionalization reactions of sulfoximines with sulfoxonium ylides are described. The combination of [RuCl2(p-cymene)]2 and a pseudo-C 2-symmetric binaphthyl monocarboxylic acid furnished the S-chiral products in 76:24–92:8 er.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…With previous reports on enantioselective C−H alkylation/cyclization reactions of sulfoximines with sulfoxonium ylides by Shi [6d] and our group [6f] in mind, we investigated the reaction of sulfondiimine 1 a and sulfoxonium ylide 2 a using the combination of a metal catalyst and chiral carboxylic acid, which enables carboxylate‐assisted enantioselective C−H activation (Table 1). [11–13] After intensive screening of the reaction conditions, we found that the desired product ( 3 aa ) was obtained in the presence of [Ru( p ‐cymene)Cl 2 ] 2 , AgOTf, and a chiral carboxylic acid ligand.…”
Section: Methodsmentioning
confidence: 99%
“…With previous reports on enantioselective C−H alkylation/cyclization reactions of sulfoximines with sulfoxonium ylides by Shi [6d] and our group [6f] in mind, we investigated the reaction of sulfondiimine 1 a and sulfoxonium ylide 2 a using the combination of a metal catalyst and chiral carboxylic acid, which enables carboxylate‐assisted enantioselective C−H activation (Table 1). [11–13] After intensive screening of the reaction conditions, we found that the desired product ( 3 aa ) was obtained in the presence of [Ru( p ‐cymene)Cl 2 ] 2 , AgOTf, and a chiral carboxylic acid ligand.…”
Section: Methodsmentioning
confidence: 99%
“…The fluorescence emission properties of 99d were surveyed, and the indole-derived Weinreb amide 103b could act as a chiral ligand in the Cp*Rh( iii )-catalyzed asymmetric [4+2] annulation of sulfoximine with α-diazo acetyl acetate. 63 Very recently, the construction of axially chiral trisubstituted olefins was also achieved by the same group, which is more challenging in view of their much lower racemization barriers compared with tetrasubstituted alkenes. 64…”
Section: Asymmetric Alkyne Functionalization Strategymentioning
confidence: 99%
“…Notably, the desymmetrization strategies require the use of diarylsulfoximine substrates bearing two identical aromatic rings. The development of a catalytic asymmetric reaction with broader substrate scope could achieve diverse synthesis of chiral thiadiazine 1-oxides and thus remains highly desirable.…”
Section: Introductionmentioning
confidence: 99%